The scarcity and distribution of rainfall drove the performance (i.e., mitigation of N oxide emissions, crop yield and quality) of calcium ammonium nitrate management in a wheat crop under rainfed semiarid conditions. Issue 13 (9th November 2020) - Guardia, Guillermo; González-Murua, Carmen; Fuertes-Mendizábal, Teresa; Vallejo, Antonio
ABSTRACT: Selection and management of synthetic nitrogen (N) fertilizers, including nitrification inhibitors, are considered an effective strategy to mitigate N oxide emissions, but depends strongly on soil characteristics and climatic conditions. We evaluated the effect of the use of a nitrification inhibitor (2-(3, 4-dimethyl-1H-pyrazol-1-yl) succinic acid isomeric mixture (DMPSA)) or splitting calcium ammonium nitrate (CAN) on the N oxides and CH4 emissions, yield, N use efficiency (NUE) and bread-making quality in a winter wheat ( Triticum aestivum L.) crop. During a typical rainfall cropping season, neither splitting CAN nor using DMPSA reduced significantly the area-scaled or yield-scaled emissions in comparison to a single application of CAN without inhibitors. This could be explained by the low emissions in CAN amended plots. Conversely, in the subsequent extremely dry cropping season, higher N oxide peaks occurred after soil rewetting and the effectiveness of DMPSA was significant in these conditions (e.g. 83% mitigation for NO). No improvement in the NUE, yield or bread-making quality was achieved with a split application or DMPSA added to the fertilizer. Under the conditions of the study, splitting CAN should not be recommended from a yield-scaled emissions viewpoint, while the use of DMPSA may be encouraged due to large variability in the amount and distribution of rainfall.